Reference items in agricultural articles - Viswanathan, Vijaya Lekshmi (Journal of Modern Languages, 2017)
The structure of connected discourse is considered a topic of primary importance in current linguistic theory and is closely linked with semantic structure and its relation to syntax. However, it was only in 1973 that there was a more positive change in attitude towards discourse structure studies when Charles Ruhl considered the rhetorical notion of coherence, mentioning the Prague School linguists and Halliday in his article 'Language Sciences 25, Prerequisites for a Linguistic Description of Coherence'. And in 1976, Michael Halliday and Ruqaiya Hasan further delved into this area in their 'Cohesion in English', using systemic functional grammar and focusing on text rather than the clause.